Microbiota, Phagocytic Activity, Biochemical Parameters and Parasite Control in Horses with Application of Autochthonous, Bacteriocin-Producing, Probiotic Strain Enterococcus faecium EF 412 - Lauková, Andrea; Micenková, Lenka; Kubašová, Ivana; Bino, Eva; Kandričáková, Anna; Plachá, Iveta; Štrkolcová, Gabriela; Gálik, Branislav; Kováčik, Anton; Halo, Marko; Simonová, Monika Pogány (Probiotics and antimicrobial proteins, 2023)
The beneficial influence of bacteriocin-producing, probiotic, mostly non-autochthonous bacteria has already been reported in various animals. However, their use in horses provides limited information, and results with autochthonous bacteria have not been reported. Therefore, the main objective of this model study was to test the effect of autochthonous, bacteriocin-producing faecal strain Enterococcus faecium EF 412 application in horses. One gram of freeze-dried EF 412 strain (109 CFU/mL for 21 days) was applied to horses in a small feed ball. Clinically healthy horses (12), Slovak warm-blood breed of various ages (5-13 years), were involved in a 35-day-long experiment, also functioning as control for themselves. They were stabled in separate boxes (university property), fed twice a day (hay, whole oats or grazed) with water access ad libitum. Sampling was performed at the start of the experiment, i.e. at days 0/1, 21 (3 weeks of EF 412 application) and at day 35 (2 weeks of EF 412 cessation). EF 412 colonized GIT of horses was 3.54 ± 0.75 CFU/g (log 10) at day 21. The eggs of the nematode Strongylus spp. were not found in horses after EF 412 application, and Eimeria spp. oocysts were similarly not found. The other microbiota were not reduced as evaluated by the use of standard method. Using next-generation sequencing, at phylum level, phyla Bacteroidetes and Firmicutes dominated and at family level, they were Bacteroidales BS11 and S24-7 gut goups and Lentisphaerae. In horses, the increasing tendency in phagocytic activity was noted after EF 412 application. Biochemical parameters were in the physiological range. Total protein value was significantly decreased at day 21 compared with day 0/1 as well as with day 35 (P < 0.05). Cholesterol and triglycerides were influenced (decreased) at day 21 compared with day 0/1 and day 35. Neither nematode eggs Strongylus spp. nor Eimeria spp. oocysts were found in faeces after EF 412 application. Autochthonous, faecal strain E. faecium EF 412 showed promising application potential.
Keywords: Bacteriocins; kontrola infekčních nemocí; zvířata; feces; Biochemical parameters; bakteriociny; Parasites; koně; Health; Feces; mikrobiota; probiotika; Horses; Communicable Disease Control; Probiotics; Animals; Beneficial strain; Enterococcus faecium; Microbiota